1999
DOI: 10.1021/ef9801773
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics of Carbon:  Influence of the Zone I−Zone II Transition on Burn-Out in Pulverized Coal Flames

Abstract: Transition of reaction from Zone II to Zone I during char combustion in a pulverized coal (pc) flame is shown to result in significant and discontinuous drop, jointly, in temperature and in reaction rate, with a correspondingly significant increase in burn-out time. In the particular case studied, as example, the estimated increase in burn-out time is by a factor of at least 3. The reduction in reaction rate is partly due to a (300 °C) drop in temperature, but it is jointly due to the doubling of the (operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…However, there are few data available for high-temperature oxidation. It is well known that, for the combustion of porous carbon particles, with increasing temperature, there is a transition from regime I to regime II (from reaction-controlled to diffusion-controlled). , It has also been shown that the reaction rate in the diffusion-controlled zone (regime II) is proportional to the square root of the rate constant . Because the intrinsic reaction activation energy is related to the reaction rate constant through the Arrhenius equation, the apparent activation energy for the reaction should be 1/2 the intrinsic activation energy of the reaction.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…However, there are few data available for high-temperature oxidation. It is well known that, for the combustion of porous carbon particles, with increasing temperature, there is a transition from regime I to regime II (from reaction-controlled to diffusion-controlled). , It has also been shown that the reaction rate in the diffusion-controlled zone (regime II) is proportional to the square root of the rate constant . Because the intrinsic reaction activation energy is related to the reaction rate constant through the Arrhenius equation, the apparent activation energy for the reaction should be 1/2 the intrinsic activation energy of the reaction.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…In this study, the correlations for Sherwood number and Nusselt number are [17] Nu ‫ס‬ 2.0 ‫ם‬ 0.60 Re Pr (11) These correlations allow the HP-CBK model to be used for large-particle char oxidation. The boundary layer diffusion is modeled in a manner similar to that used by Mitchell et al [15], taking Stefan flow into account [18].…”
Section: Boundary Layer Diffusionmentioning
confidence: 99%
“…A more mechanistically meaningful representation of the intrinsic reaction rate is a Langmuir-Hinshelwood form [6,9], which in its simplest form becomes the Langmuir rate equation: In an attempt to treat effects of pressure, Essenhigh proposed a so-called second effectiveness factor [10] to account for the internal combustion. The second effectiveness factor was calculated from the power index of the normalized density-diameter relationship [5,10,11]:…”
Section: Introductionmentioning
confidence: 99%
“…To study the reaction-diffusion processes within the complicated porous media, previous models have mostly based on dimensionless groups, such as Damköhler number, Thiele modulus, and the corresponding external/internal effectiveness factors, which were defined based on Fick’s diffusion law using empirical effective diffusion coefficients and idealized pellet shapes. As gas diffusion in complicated pores does not follow Fick’s law, and actual pore microstructures are not considered directly, , these models and indexes, though helpful, are often used on a phenomenological and qualitative basis. , …”
Section: Introductionmentioning
confidence: 99%
“…As gas diffusion in complicated pores does not follow Fick's law, 17 and actual pore microstructures are not considered directly, 23,24 these models and indexes, though helpful, are often used on a phenomenological and qualitative basis. 26,27 Since the pore structure in actual porous media is too complicated to be described integrally and elaborately, it is meaningful to first focus on some typical structures at microscale and try to characterize the coupling of reaction and diffusion in a more quantitative way. For this purpose, molecular dynamics (MD) simulation can be used as a powerful tool in that the complicated diffusion and reaction processes are reproduced by the basic motion of the microscopic elements, rather than numerically computed from their material properties or statistical correlations, which are hard to obtain at this scale.…”
Section: Introductionmentioning
confidence: 99%